Financial Factors and the Macroeconomy - a Policy Model - Leif Brubakk; Paolo Gelain (Norges Bank, 2014)
This paper documents the theoretical structure of an extension of the Norges Bank policy model NEMO. New features include an explicit treatment of the credit market, including a separate banking sector, a role for housing services and house prices, and the option of using macro-prudential instruments as the LTV-ratio and capital requirements as policy instruments. The model rely on building blocks from the recent literature on the interaction between the financial sector and the real economy.
hdl:11250/2506909
Keywords: 330; DSGE; credit market frictions; banking sector